HEALTH CARE PLANNING IN SELECTED DEVELOPING COUNTRIES. - Jabrullah, A. H., WH, W. F. F., Noor Amanina, S., Mesk, Z., Rosliza, A. M., & Juni, M. H. (International Journal of Public Health and Clinical Sciences, 2017)
Background: Health planning in developing countries differs from developed countries. They have more limited resources for health development. Therefore efficient health planning and resource allocation is critical to ensure optimal health outcome of the nation. Due to the nature of heterogeneity among the developing countries, the health approach may differ contextually among developing countries. This paper aims to compare practices of health planning development among selected developing countries. Materials and Methods: This review encompasses relevant scientific articles and most recent official country report related to health planning. Searches only include articles or reports published in English. Based on the six WHO regions. Selection of countries based on availability of manuscript (article and report) fulfilling the criteria. The countries selected were Bangladesh, Belize, Jordan, Kenya, Malaysia and Turkey. Result: A five or ten years of strategic plan for health is the most practiced among the studied developing country. It usually involves multi-sectorial within the country and international agencies and consultants. The advancement of technology helps in improving the administrative data utilisation to allow informed-decision making, deeper root cause analysis and timely monitoring and evaluation. Other than that, engagement with various stakeholders from different level – at all phase of plan development, together with political will is the key factor of the successful implementation. Despite that, these developing countries often suffer from limited resources in term of workforce, financing and technical expertise. Conclusion: Although the health planning process is similar across countries studies, where the cycles start with situational analysis, prioritisation, options appraisal, implementation, monitoring and lastly evaluation. Each country may have slightly different approaches, depending on their context, resources and technology capacity.
Keywords: health care, planning, planning framework, developing countries